Bringing multimedia contents into MP3 files. - Egidi, Lavinia (IEEE Communications magazine)
The digital music revolution has improved the availability of music and made it easier to enjoy. The shift from hard support, such as audio CDs, to software leaves some unsatisfied by the loss of additional media contents, such as images, lyrics, and CD cover. We propose to fill the gap by enriching e-music with multimedia contents. Our proposal focuses specifically on MP3 as a widely distributed open format. The challenge we meet in enriching MP3 lies in maintaining audio compatibility and avoiding file size explosion. To this end, we define a description language to express multimedia contents in a textual way, with higher representation efficiency than existing languages. We also address security issues that arise from the use of an open format. Effectiveness is shown with an MP3 player capable of rendering multimedia contents.